Expressiveness as a Category of Piano-Performance Musicology - A. Yu. Rumyantseva (Культура України, 2018)
The aim of the paper is to substantiate the author’s definition of “expressiveness” in the context of piano art based on the system analysis of the “performer’s expressiveness” phenomenon. Research methodology. The article uses the fundamental, general scientific methods and the principles of scientific knowledge, in particular, dialectical, culturological ones, as well as the methods of objectivity, analysis and synthesis, deduction and induction, the methods of systemic, terminological and comparative analysis. Results. Based on the systematic analysis of the “expressiveness” phenomenon in the musical, and particularly, in the piano performance, the essence and structure of the mentioned phenomenon have been discovered. Its components have been defined and the specific features  have been developed. The paper suggests the author’s definition of “expressiveness” phenomenon in the context of the piano performance. It has been noted that it is based on the mutually combining and influencing components of the means of expressiveness system: tempo metro-rhythm, melodic intonation means, carcass and pedalization, timbre dynamics. It has been proven that only cohesive use of all the components of the system of the performer’s expressiveness makes it possible to show the emotional programme and display the artistic contents of the composition. It has been concluded that the expressiveness in the piano performance is a complex of individual piano tricks that, when using in the interpretation, helps unfold the emotional program and artistic content of the composition, as well as show the artistic thought of the composer most accurately. Novelty. An attempt is made to present a systematic analysis of “expressiveness” phenomenon in the music performance art. The author’s definition of “expressiveness” phenomenon is given in the context of the piano performance. The practical significance. The information contained in the article can be used in the lectures of the piano classes, as well as in the courses of lectures in “Theory of Music” and “Music Interpretation”.